Respiratory Syncytial Virus Transplacental Antibody Transfer and Kinetics in Mother-Infant Pairs in Bangladesh - Chu, Helen Y. (J Infect Dis, 2014)
Background. Pneumonia is the leading cause of childhood mortality globally. Respiratory syncytial virus (RSV) is the most important viral cause of pneumonia. Maternal serum antibody protects infants from RSV disease. The objective of our study was to characterize RSV antibody levels in mother-infant pairs. Methods. Serial serum samples were collected from mother-infant pairs in Bangladesh from the third trimester of pregnancy to 72 weeks postpartum and tested using an RSV antibody microneutralization assay. Serologic infection was defined as a 4-fold increase in antibody titer. Maternal antibody half-life was calculated using infant antibody titers from birth to 20 weeks. Results. The ratio of infant cord blood to maternal serum RSV antibody titers in 149 mother-infant pairs was 1.01 (95% confidence interval [CI], .99–1.03). Maternal RSV antibody titers in the third trimester and at birth were strongly correlated (R = 0.68). Antibody half-life was 38 days (95% CI, 36–42 days). Higher cord blood RSV antibody titers were associated with a lower risk of serologic infection (P = .01) and maintenance of antibody titer above a potentially protective threshold (P < .001). Conclusions. Efficient transplacental transfer of RSV-specific antibody from mother to the fetus was documented in mother-infant pairs in Asia. Higher cord blood antibody titers were associated with protection from serologic infection.